From cryptic to colorful: Evolutionary decoupling of larval and adult color in butterflies. Issue 1 (1st February 2020) - Medina, Iliana; Vega-Trejo, Regina; Wallenius, Thomas; Symonds, Matthew R. E.; Stuart-Fox, Devi
Abstract: Many animals undergo complete metamorphosis, where larval forms change abruptly in adulthood. Color change during ontogeny is common, but there is little understanding of evolutionary patterns in these changes. Here, we use data on larval and adult color for 246 butterfly species (61% of all species in Australia) to test whether the evolution of color is coupled between life stages. We show that adults are more variable in color across species than caterpillars and that male adult color has lower phylogenetic signal. These results suggest that sexual selection is driving color diversity in male adult butterflies at a broad scale. Moreover, color similarities between species at the larval stage do not predict color similarities at the adult stage, indicating that color evolution is decoupled between young and adult forms. Most species transition from cryptic coloration as caterpillars to conspicuous coloration as adults, but even species with conspicuous caterpillars change to different conspicuous colors as adults. The use of high-contrast coloration is correlated with body size in caterpillars but not adults. Taken together, our results suggest a change in the relative importance of different selective pressures at different life stages, resulting in the evolutionary decoupling of coloration through ontogeny.